Pengaruh waktu aging terhadap perubahan sifat fisik paduan ingat bentuk (shape memory alloy) Cu-Zn-Al - Rico Josua; Budiarto Budiarto (Universitas Muhammadiyah Metro, 2023)
Cu-Zn-Al alloy is a shape memory alloy (SMA) that is widely used due to its high transformation temperature. This study aimed to determine the effect of variations in aging time (1.3 and 5 hours) on physical changes (crystal structure and hardness) in Cu-Zn-Al alloys. The method used in this study is powder metallurgy by combining Cu, Zn, and Al powders. Followed by mixing them and then compacting the alloy. The alloy was sintered at 400°C and quenched at room temperature for 24 hours. Then the alloy was given various heat treatments (aging) for 1.3 and 5 hours at 200 °C. Microstructure and hardness tests were carried out on Cu-Zn-Al alloys to determine the properties of the alloy after being treated. From the test, it was found that the hardness value increased from 303 HBN to 375 HBN (1 hour), 351 HBN (3 hours), and 320 HBN (5 hours), and there was a change in crystal size, dislocation density, and lattice strain.